ИЖТИМОИЙ ИДЕНТИКЛИК ПСИХОЛОГИК ФЕНОМЕН СИФАТИДА - Хўжаев, Ф. (SCIENCE and SOCIETY, 2021)
This article describes in detail the concept of social identity, which is one of the current problems in the science of psychology. In particular, the analysis of definitions is described given by foreign psychologists in relation to the term social identity.